Religious Character of Elementary School Trough Gusjigang Values - Zulfiyah, Rizqiyatul 'Izzah; Ermawati, Diana; Fardani, Much Arsyad (Universitas Muhammadiyah Makassar, 2024)
Integrating values in Gusjigang can be done through extracurricular and co-curricular activities in the context of building student character. Therefore, the purpose of this study is to analyze the form of student activity as a reflection of Gusjigang values in shaping students' religious character. This research uses a descriptive qualitative research type with six grade 5 students as research subjects. Data collection techniques are carried out by observation, interviews, and documentation. Data analysis techniques use the Miles and Huberman model, namely data reduction, data presentation, and verification or conclusions. Test the validity of the data in this study using four tests according to Sugiyono namely credibility, transferability, dependability, and confirmability. The results of this study indicate that the value of Gusjigang can be reflected in all forms of student activity consisting of habituation, co-curricular and extra-curricular activities. In relation to character formation, there are five forms of student activity as a reflection of the